Japanese subcultural event participants in Malaysia and their personal development: preliminary findings - Yamato, Eriko (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Japanese subcultural products such as animations (anime), comics (manga) and role playing games have been produced primarily for the Japanese domestic market, yet a large amount are disseminated outside Japan. Consumption of these products is also extended to fan activities such as costume play (cosplay) of anime/manga/game characters and production of secondary products such as art works and fan magazines. There are noticeable numbers of events for anime/manga/game fans organized by students’ clubs at universities and youth groups even in Malaysia. Youth subculture including fan activities is often appraised negatively as an undesirable anti-social activity for personal development of youth. Subcultural event participation also might not be perceived positively by those who have never experienced it. Thus, the study was designed to understand experiences of Malaysian youth who are participating in Japanese subcultural events. This paper reports on preliminary findings from this study. In-depth interviews were conducted with youths who have participated in the events for more than 5 years. Their experiences were analysed by referring recent discussions to personal development models. These youth described their activities as a new culture and their parents’ generation has negative perception of this culture. However, their descriptions indicate not only temporary enjoyment but also enhancement of their self-knowledge, and development of their social abilities.